Occupational competence in modern production structures : development of competences for the production of tomorrow - Scheib, Thomas [Verfasser] (My University, 2009)
"Modern production concepts and holistic production systems from the basis for current and future production. The main focus is on consitent process orientation and the streamlining of these processes. The effects of these developments extend to exerting a direct impact on operative employees rather than merely affecting executive management and require new and changed competences. The present paper concentrates on presenting these new competences and other competences gaining in significance. It also highlights further competences of relevance due to teamwork, the characteristic feature of modern production concepts alongside process orientation. This "broad-based" development necessitates a widening of and a change in our understanding of occupational competence in overall terms. The paper concludes by outlining a profile for employability skills for skilled work within modern production concepts." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; G 1.2.3.2 Anforderungen & Bedarfe; Handlungskompetenz; Kompetenzentwicklung; Facharbeit; Produktionsbereich; Prozessorientierung; Teamfähigkeit; Kompetenzprofil